2017
DOI: 10.5089/9781475589207.001
|View full text |Cite
|
Sign up to set email alerts
|

Managing the Tide: How Do Emerging Markets Respond to Capital Flows?

Abstract: IMF Working Papers describe research in progress by the author(s) and are published to elicit comments and to encourage debate. The views expressed in IMF Working Papers are those of the author(s) and do not necessarily represent the views of the IMF, its Executive Board, or IMF management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
43
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 26 publications
2
43
0
1
Order By: Relevance
“…During this period, some countries, especially those receiving large capital inflows, employed macroprudential policies to contain credit expansion and financial sector risks. As the global crisis took hold, macroprudential instruments were used to support credit and economic recovery (Ghosh et al, 2017).…”
mentioning
confidence: 99%
“…During this period, some countries, especially those receiving large capital inflows, employed macroprudential policies to contain credit expansion and financial sector risks. As the global crisis took hold, macroprudential instruments were used to support credit and economic recovery (Ghosh et al, 2017).…”
mentioning
confidence: 99%
“…Finally, in more recent studies, Ghosh et al . () examine how emerging market economies respond to capital inflows using quarterly data over the period 2005–2013, and they show that intervention in the foreign exchange market to resist currency appreciation pressures is one of their possible policy tools. In the same way, Fratzscher et al .…”
Section: Introductionmentioning
confidence: 99%
“…4 Jeanne and Korinek (2010) and Bianchi (2011) showed that there are pecuniary 2. For details, see, for example, Jongwanich and Kohpaiboon (2012), Ahmed and Zlate (2014), Forbes et al (2016), and Ghosh, Ostry, and Qureshi (2017).…”
Section: Introductionmentioning
confidence: 99%
“…For details, see, for example, Jongwanich and Kohpaiboon (), Ahmed and Zlate (), Forbes et al (), and Ghosh, Ostry, and Qureshi ().…”
mentioning
confidence: 99%